2022
DOI: 10.1093/jxb/erac329
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proteostasis, lipid remodeling, and nitrogen remobilization define barley flag leaf senescence

Abstract: Leaf senescence is a developmental process allowing nutrient remobilization to sink organs. We characterized flag leaf senescence at 7, 14 and 21 days past anthesis (dpa) in two near-isogenic barley lines varying in the allelic state of the HvNAM1 transcription factor gene, which influences senescence timing. Metabolomics and microscopy indicated that, as senescence progressed, thylakoid lipids were transiently converted to neutral lipids accumulating in lipid droplets. Senescing leaves also exhibited an accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Similarly, LOX3-RFP, a type 13 lipoxygenase, could clearly be traced to protrusions in the plastid membrane (Figure 7 A, bottom). In addition, changes in genes involved in the jasmonic acid pathway and massive plastid lipid remodeling were reported in barley flag-leaf senescence that could involve lipoxygenase activity (Cohen et al, 2022). Such scenario is consistent with lipoxygenase-dependent osmotic stress-induced plastid breakdown shown here.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LOX3-RFP, a type 13 lipoxygenase, could clearly be traced to protrusions in the plastid membrane (Figure 7 A, bottom). In addition, changes in genes involved in the jasmonic acid pathway and massive plastid lipid remodeling were reported in barley flag-leaf senescence that could involve lipoxygenase activity (Cohen et al, 2022). Such scenario is consistent with lipoxygenase-dependent osmotic stress-induced plastid breakdown shown here.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis further revealed that genes related to lipid metabolism, including fatty acid and wax, were significantly up-regulated in SS under light conditions (Figure 5C). We expected that this might be due to lipid homeostasis and turnover being disrupted in SS foxtail millet during the developmental process, resulting in an accelerated senescence phenotype in response to environmental stress [42,43]. Furthermore, we observed that genes up-regulated in LS during DIS were largely associated with photosynthesis and chlorophyll metabolism (Figure 5B,D), which is in line with the beginnings of leaf senescence and might explain the conspicuous difference in the chlorophyll content and photosynthetic capacity between LS and SS [44,45].…”
Section: Transcriptional Regulation Of Dark-induced Leaf Senescence I...mentioning
confidence: 99%
“…The presence of LDAP genes in the whole land plant kingdom (de Vries and Ischebeck, 2020) is consistent with the hypothesis that LDs may accumulate in leaves of every land plants. LDs accumulate in senescing leaves (Lersten et al, 2006;Brocard et al, 2017;Zhang et al, 2020;Cohen et al, 2022) where they are supposed to sequester galactolipid-derived FAs before conversion into phloem-mobile sucrose (Kaup et al, 2002). TAG synthesis has been demonstrated to occur in leaves, yet only a very limited TAG content was detected in Arabidopsis senescent leaves (Slocombe et al, 2009;Yang and Ohlrogge, 2009), suggesting this TAG accumulation is transient.…”
Section: Lds In Leaves Play Different Functions Ld Abundancy In Leave...mentioning
confidence: 99%